An Analysis of Shadow Education on Mainstream Education in Public Secondary Schools in Athi River District - Mwania, Johnson K.; Moronge, Dr. Makori (African Journal of Education and Practice, 2016)
Purpose: The purpose of this study was to analyse the impacts of shadow education on mainstream education in secondary schools in Athi River District. Methodology: The study used descriptive survey research design. This study used primary data which was collected through use of structured questionnaires. The target population of the study were teachers, students and parents in public secondary schools in the 29 secondary schools in Athi River District. Purposive sampling was used to select respondents from the sampling frame; 29 principals, 29 teachers, 29 parents and another 29 students were selected from the twenty nine schools. Data from the questionnaires were analysed using Statistical Packages for Social Sciences (SPSS) to derive descriptive results Results: The findings implied that performance is an important element that is considered in shadow education. The study findings indicated that shadow education does not assist in coverage of syllabus, but improves teachers' motivation and students' performance. Further, descriptive studies also show that shadow education affects the time parents spend with their children. Unique contribution to theory, practice and policy: The study provides recommendation to the government to reduce the regulatory burden on shadow education and to parents to encourage their children to value shadow education. The study recommends further studies to touch on the implication of shadow education costs to the income of households in Kenya-either in the rural or urban setting.